(untitled) (Web of Teachers: Inderscience Research, 2025)
This article covers modern methods of management of greenhouses based on IMRAT (Scientific, Monitoring, Resource Management, Automation and Technology) requirements. The article discusses the scientific approach, real-time monitoring, rational use of resources, the importance of using automation systems and modern technologies for the effective organization of greenhouse activity.